Aristotelian concept of providence according to the evidence of ancient and early christian authors - Alexey Fokin (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2020)
The article discusses the concept of providence attributed to Aristotle by both ancient and early Christian authors. This concept was spread in two forms or versions: according to the fi rst and the main version, divine providence is limited to the celestial spheres up to the moon and does not include the earth and the sublunar area. The second implied that providence either covers only the most important areas of the world, or the world as a whole, including the earth, but sustains the existence common genera and species of creatures, and does not care for specifi c individuals and their needs. The author of the article shows that Aristotle himself never applied the concept of providence to his god, i. e. to the Prime Mover, which moves everything without being moved, and to the Intellect, which thinks only of itself. This concept was never used by Aristotle in a cosmological context either, but is found exclusively in an ethical or political and legal contexts, where it means “prudence”, “foresight”, or “intent”. At the same time, it is noted that the two aforementioned versions of the Aristotelian concept of providence either go back to the philosophy of Aristotle himself and his dualistic cosmology, which involves the division of the universe into two main parts, i.e. supralunar, containing celestial bodies and the sphere of motionless stars, consisting of ether and abiding in eternal and uniform circular motion, and the sublunar part, consisting of the four elements and composite bodies subject to the processes of generation and destruction; or go back to the interpretation of Aristotelian cosmology by later Peripatetics, such as Theophrastus, Critolaus, the author of the pseudo-Aristotelian treatise “De mundo” and Alexander of Aphrodisias. The article demonstrates that the Aristotelian concept of providence in all its forms was fi ercely criticised by both ancient philosophers (Platonists and Stoics) and Christian theologians, beginning with early Christian apologists and ending with late Byzantine authors.